2013
DOI: 10.1007/s00408-013-9492-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and Ventilatory Response During Exercise in COPD Patients With and Without β Blockade

Abstract: Exercise capacity and gas exchange remain unaffected in patients with COPD in the presence of BB, although heart rate and blood pressure are lower. These findings imply that BB does not adversely affect functional capacity in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…26 However, we kept individuals who used this medication in our study sample because exercise capacity remained unchanged during ␤-blocker use in a study by Thirapatarapong et al 26 In their study, individuals with COPD with and without ␤-blocker medications were compared in a maximum exercise test, and no difference was found in exercise capacity and ventilatory demand among the groups. 26 Other studies also included individuals using this medication in their heart rate analysis and demonstrated that there is no influence of ␤ blockers on analyzed outcomes. 1,23 Thus, the clinical applicability of our results can be considered more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, we kept individuals who used this medication in our study sample because exercise capacity remained unchanged during ␤-blocker use in a study by Thirapatarapong et al 26 In their study, individuals with COPD with and without ␤-blocker medications were compared in a maximum exercise test, and no difference was found in exercise capacity and ventilatory demand among the groups. 26 Other studies also included individuals using this medication in their heart rate analysis and demonstrated that there is no influence of ␤ blockers on analyzed outcomes. 1,23 Thus, the clinical applicability of our results can be considered more generalizable.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypoxemia leading to high hypoxic drive does not seem to contribute to poor ventilatory efficiency in overlap [44]; however, few hypoxaemic patients were enrolled in previous studies [41,43,44]. Although β-blockers failed to decrease the V′E/V′CO 2 nadir in COPD [39], the impact of prospective pharmacological interventions on ventilatory efficiency remains unknown in COPD-heart failure overlap and in COPD patients with out-of-proportion pulmonary hypertension. Potential improvements in ventilatory efficiency might prove valuable to decrease exertional dyspnoea and improve exercise tolerance in selected patients, particularly when cardiocirculatory abnormalities predominate over mechanical constraints (table 2) [38].…”
Section: Impact Of Co-morbidities On Ventilatory Efficiencymentioning
confidence: 99%
“…Thus, single- [51] and double-lung [61] transplantation and lung volume reduction surgery [63,66] lessened VD and increased VT thereby reducing VD/VT with consequent benefits to ventilatory efficiency. This suggests that the marked effects of these interventions on VD/VT (which would lessen V′E) relatively outweighed the consequences of lower mechanical constraints, which would otherwise increase V′E [39,[46][47][48][49][98][99][100]. Lower neural drive (e.g.…”
Section: Effects Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparison of bisoprolol and placebo in patients with moderate-to-severe COPD, there was a significantly worsening of dynamic hyperinflation during cycle endurance while exercise duration was unaltered [57]. In a study comparing 24 COPD patients on beta-blockers matched to patients not taking beta-blockers there was no difference in exercise capacity or gas exchange despite lower heart rate and blood pressure, in turn suggesting great oxygen delivery per heart beat [58].…”
Section: Choice Of Beta-blocker and Effects On Pulmonary Functionmentioning
confidence: 99%